2022
DOI: 10.1016/j.jss.2021.08.042
|View full text |Cite
|
Sign up to set email alerts
|

Use of Preoperative Laboratory Testing Among Low-Risk Patients Undergoing Elective Anorectal Surgery

Abstract: Background: Many low-risk patients receive preoperative laboratory testing (PLT) prior to elective outpatient surgery, with no effect on postoperative outcomes. This has not been studied in patients undergoing anorectal surgery. The aim of this study was to determine if PLT in this population was predictive of perioperative complications. Materials and Methods:The 2015-2018 National Surgical Quality Improvement Program (NSQIP) databases were queried for elective ambulatory anorectal surgeries. PLT was defined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 16 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…Several institutions have evaluated their independent practices and found persistently high utilization of routine preoperative testing. 13,14 This finding has been further identified in various national cohorts [15][16][17][18][19][20][21][22] culminating in the 2022 study by Taylor et al using 2017 ACS-NSQIP data from 111,589 low-risk patients, which demonstrated that 51.6% of low-risk patients received at least one preoperative laboratory test. 12 The present study adds an assessment of 8 years prior and 6 years following the introduction of the ASA guidelines equating to an analysis of 972,431 low-risk patients, suggesting that the majority of low-risk patients continue to undergo testing not recommended by the ASA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Several institutions have evaluated their independent practices and found persistently high utilization of routine preoperative testing. 13,14 This finding has been further identified in various national cohorts [15][16][17][18][19][20][21][22] culminating in the 2022 study by Taylor et al using 2017 ACS-NSQIP data from 111,589 low-risk patients, which demonstrated that 51.6% of low-risk patients received at least one preoperative laboratory test. 12 The present study adds an assessment of 8 years prior and 6 years following the introduction of the ASA guidelines equating to an analysis of 972,431 low-risk patients, suggesting that the majority of low-risk patients continue to undergo testing not recommended by the ASA.…”
Section: Discussionmentioning
confidence: 86%
“…Several institutions have evaluated their independent practices and found persistently high utilization of routine preoperative testing 13,14 . This finding has been further identified in various national cohorts 15–22 culminating in the 2022 study by Taylor et al. using 2017 ACS‐NSQIP data from 111,589 low‐risk patients, which demonstrated that 51.6% of low‐risk patients received at least one preoperative laboratory test 12 .…”
Section: Discussionmentioning
confidence: 95%
“…However, evidence suggests that routine laboratory tests are not necessary for screening: studies have shown that in almost 50% of cases, routine laboratory screening (such as routine blood and urine tests, blood grouping, chest X‐ray, and electrocardiogram) is not indicated for some patients. 8 , 9 , 10 In another study, although 12% of clinical tests were abnormal, only 0.5% of abnormal results affected clinical decision‐making. 11 In another study evaluating preoperative laboratories in patients undergoing posterior spinal fusion for idiopathic scoliosis, Clark et al 12 found that 94.9% of patients had one or more abnormal preoperative laboratory values, but only 11.7% of patients took further measure.…”
Section: Introductionmentioning
confidence: 96%
“…In the age of value‐first medicine, preoperative screening has been justified by citing concerns about patient safety and medico‐legal risks, the perception that other doctors expect preoperative testing, and that the medical benefits outweigh the medical risks, thereby making them cost‐effective. However, evidence suggests that routine laboratory tests are not necessary for screening: studies have shown that in almost 50% of cases, routine laboratory screening (such as routine blood and urine tests, blood grouping, chest X‐ray, and electrocardiogram) is not indicated for some patients 8–10 . In another study, although 12% of clinical tests were abnormal, only 0.5% of abnormal results affected clinical decision‐making 11 .…”
Section: Introductionmentioning
confidence: 99%
“…After taking informed consent, data was collected using a self-administered questionnaire that was developed after extensive literature review of previous related studies. [7][8][9]11,12 The questions relevant to the study were asked specific to laboratory, radiology and cardiology investigations conducted as part of the preoperative assessment at our institution. All efforts were made to make it brief and participant-friendly.…”
Section: Introductionmentioning
confidence: 99%